Incidence of post‐induction hypoxemia in children and the effect of induction gas composition. Issue 7 (17th March 2021) - Cumin, David; Baker, Paul A.; Anderson, Brian J.
Abstract : Background: Pediatric preoxygenation and inhalation induction of anesthesia can include a mixture of gases. In children, the clinical impact on oxygenation while using other gases with oxygen during an inhalation induction is unknown. Aim: We aimed to determine the impact of oxygen, nitrous oxide, and air concentrations added to the volatile agent by recording the incidence of hypoxemia following an inhalation gaseous induction in children. Method: Records from an Automated Information Management System were used to find the incidence of hypoxemia following an inhalation induction of anesthesia. Episodes of hypoxemia (SaO2 < 90% sustained for at least 120 s) were recorded in the 10 min after the 3‐min induction period. Nitrous oxide and oxygen concentrations were recorded and nitrogen concentration was deduced. We also considered patient sex, age, and ASA status as covariates. Results: A total of 27 258 cases were included in the analysis. The overall incidence of hypoxemia following an inhalation induction of anesthesia was 5.08% (95% CI 4.83 5.35). Hypoxemia was more common in younger patients and those with higher ASA scores. Controlling for those factors and sex, the incidence of hypoxemia increased 1.2‐fold when inspired oxygen concentration was less than 60% and hypoxemia was 2.37 times greater than the overall incidence when the inspired oxygen concentration was less than 40%. There was no clear effect of different concentrations of nitrous oxide or nitrogen when those were factored into the model. Conclusion: The risk of hypoxemia following an inhalation induction of anesthesia in children is minimized when the inspired concentration of oxygen is greater than 60%.